On little known deep-sea shark Centroscyllium ritteri (Etmopteridae, Squliformes) - Vladimir N. Dolganov (Известия ТИНРО, 2015)
Morphological description for 30 specimens of shark Centroscyllium ritteri caught off northeastern Japan in the 1980, including juveniles and adults of both sexes. Counts for vertebras, teeth rows, and intestinal valves are presented. The species biology is discussed.